Protected cultivation to boost the income of farmers in Bundelkhand region of Uttar Pradesh - Singh, R K; Rai, Mritunjay; Kumar, Arvind; Singh, Awani Kumar; Mishra, A C (Indian Horticulture, 2022)
Annual requirement of vegetables at the present rate of 180 g/day/capita is estimated to be about 135 MT against the obtained 125 MT , which clearly indicates that there is a short-fall of 10 MT of vegetables. Whereas, if the per capita consumption of FAO (300 g/day capita) is to be taken into consideration, there would be a large gap in demand and production. The actual problem of low productivity has been attributed to the extremes of temperatures ranging from 5-480C during the year which does not allow year-round vegetable cultivation at large scale. In India, this production gap is an opportunity of growing horticultural crops in protected cultivation and the area under high-tech horticulture is growing larger day-by-day and the productivity and exports have both tremendously improved. Vegetables can now be cultivated in off-season, with the induction of an artificial technique like greenhouse technology, in which temperature and moisture is controlled for specific growth of vegetables.